1991
DOI: 10.1111/j.1439-0418.1991.tb00348.x
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of willow‐species for the development of the winter moth, Operophtera hrumata (Lep., Geometridae)

Abstract: Larvae of the winter moth Operophteru brurnutu were fed on a variety of willow species which had bud burst up to 4 weeks prior to the oak bud burst. The larvae were analyzed for growth, feeding efficiency and nitrogen budgets as a function of host plant, nutrient content and temperature. Furthermore, the reproductive success of females was tested according to the host plants used as food during their larval stage.Within the temperature range from 5 O to 20 "C consumption rate (RCR) and growth rate (RGR) of lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…The linear relationship between adult female size and fecundity in insects has been reported on many occasions for the Hemiptera and other insects (e.g. WAY 1968;LEATHER and WELLINGS 1981;DIXON 1985). The existence of a curvilinear association which better describes the data has not been demonstrated so often.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The linear relationship between adult female size and fecundity in insects has been reported on many occasions for the Hemiptera and other insects (e.g. WAY 1968;LEATHER and WELLINGS 1981;DIXON 1985). The existence of a curvilinear association which better describes the data has not been demonstrated so often.…”
Section: Discussionmentioning
confidence: 78%
“…Some insects within the Hemiptera, such as certain aphids, tend to have the maximum potential number of offspring predetermined early in life based on a specific and constant ovariole number (LEATHER and WELLINGS 1981); this would dictate a maximum theoretical fecundity which in turn necessitates an upper asymptote to the size/fecundity relationship. The ability to realise this potential is likely to be a function of resources available to the female during growth, via an increase in embryos per ovariole (LEATHER and WELLINGS 1981). Thus, a very small female, whilst able to survive, might only be able to provide minimal requirements for egg production until a certain body size is reached.…”
Section: Discussionmentioning
confidence: 99%
“…Dewar & Watt (1992) predicted that climatic warming would result in decreased synchrony with budburst in Sitka Spruce ( Picea sitchensis ) and Kerslake & Hartley (1997) suggested that synchronization with Heather ( Calluna vulgaris ) is unimportant. If egg hatch occurs before or after Oak budburst, the caterpillars can disperse to other hosts (Smith 1972; Kirsten & Topp 1991), but there is little understorey in Wytham, or other mature woodlands, for them to feed on. In any case, Oak is considered to be the optimum host for Winter Moth (Wint 1983) and, because dispersal must be dangerous, it is probably a last resort.…”
Section: Discussionmentioning
confidence: 99%
“…Arnongst these physical factors leaf size, leaf toughness and the presence of trichomes all influence palatability to insects (WARING and PRICE 1988;BoGATKO 1990;BoGAGHEVA 1994;MATSUKI and MAGLEAN 1994). The nutritive value of a leaf to a developing insect, particularly the available soluble nitrogen concentration, varies throughout the growing season (THOMAS and HODKINSON 1991;KiRSTEN and ToPP 1991), with food quality declining as the leaf ages (IVlEYER and MONTGOMERY 1987). The nutritive value of a leaf to a developing insect, particularly the available soluble nitrogen concentration, varies throughout the growing season (THOMAS and HODKINSON 1991;KiRSTEN and ToPP 1991), with food quality declining as the leaf ages (IVlEYER and MONTGOMERY 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Cheniical effects are more subtle, with sornetimes a close inter-relationship apparent between the concetitrations of nutritive and defensive chemicals within the leaves (LARSSON et al 1986). The nutritive value of a leaf to a developing insect, particularly the available soluble nitrogen concentration, varies throughout the growing season (THOMAS and HODKINSON 1991;KiRSTEN and ToPP 1991), with food quality declining as the leaf ages (IVlEYER and MONTGOMERY 1987). Beyond the point of senescence, however, soluble nutrients are again mobilized and food quality may tmprove for some insects.…”
Section: Introductionmentioning
confidence: 99%